2021
DOI: 10.3906/yer-2008-14
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution temperature and precipitation variability of southwest Anatolia since 1730 CE from Lake Gölcük sedimentary records

Abstract: We report high-resolution multi-proxy analyses (lithology, µXRF and magnetic susceptibility (MS)) of two short gravity sediment cores from the crater Lake Gölcük, southwest Turkey. Our results provide a detailed hydroclimatic record for the last ~290 years. Aided with factor analysis of µXRF data and 210 Pb and 137 Cs dating, our multi-proxy data show that the Lake Gölcük records documented a series of wet and dry periods between ~ 1730 (±71) and ~ 2018(±3) CE. Wet periods are evidenced by dark olive green mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The justification is that warm summer temperatures lead to increase in precipitated calcium in water column. In fact, Danladi et al (2021) found the log(Ca/K) in Lake Gölcük to be a direct proxy for summer temperature. MS is a proxy for siliciclastic materials entering lacustrine environments and its high (low) values usually suggest high (low) input of siliciclastic materials in a lake (Thompson et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The justification is that warm summer temperatures lead to increase in precipitated calcium in water column. In fact, Danladi et al (2021) found the log(Ca/K) in Lake Gölcük to be a direct proxy for summer temperature. MS is a proxy for siliciclastic materials entering lacustrine environments and its high (low) values usually suggest high (low) input of siliciclastic materials in a lake (Thompson et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high δ 13 C and δ 18 O values between AD 450–730 imply dry climate conditions (Li and Ku, 1997; Roberts et al, 2008). The low log(Ca/K) values during this period indicate cold climate conditions (Danladi et al, 2021). Also supporting the multiproxy interpretation during this period, the dominance of Artemisia and Poaceae and low tree pollen ( Pinus , Juniperus type, Quercus [deciduous and evergreen]) suggest the prevalence of steppe vegetation under dry climate conditions.…”
Section: Lake Gölcük Climate Change Through Timementioning
confidence: 97%
See 2 more Smart Citations